Analisis Yuridis Putusan Mahkamah Konstitusi Tentang Penetapan Pasangan Calon Presiden dan Wakil Presiden Terhadap Penegakan dan Kepastian Hukum di Indonesia - Muhdar Muhdar; Tri Susilowati (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
On this basis, the equal position between these institutions has the potential to give rise to electoral conflict, therefore the institution of the Constitutional Court was born as a mediator of possible conflicts. Another authority that the Constitutional Court has is judicial review of the Constitution. This authority previously belonged to the MPR before the amendment. The Constitutional Court has the principle in making judicial review decisions that apply to everyone (erga omnes), and are final (no other legal remedies) and appeal (binding for all parties). After the third constitutional amendment, a new issue has now arisen from the Constitutional Court, which should be the institution of the Constitutional Court as the highest court in the Republic of Indonesia. In fact, a problem has arisen from the Institution of the Constitutional Court which should be able to maintain the dignity and stability and trust of the Indonesian people. What is currently being discussed is the Constitutional Court (MK) Decision Number 90/PUU-XXI/2023 concerning the age requirements for presidential candidates (capres) and vice presidential candidates (cawapres) which has resulted in controversy. The decision contains a material review of the age requirements for presidential and vice presidential candidates as stated in Article 169 letter q of Law Number 7 of 2017 concerning Elections. Upon granting some of the material tests, someone who is not yet 40 years old can run as a presidential or vice presidential candidate if they have experience as a regional head or other official elected through elections. Thanks to this MK decision, President Joko Widodo's eldest son who is also the Mayor of Surakarta, Gibran Rakabuming Raka, who is only 36 years old, can run as vice presidential candidate. This decision became polemic because it was made by Chief Justice of the Constitutional Court Anwar Usman, who is Jokowi's brother-in-law and Gibran's uncle. After the Constitutional Court's decision, accusations emerged about political dynasties, even nepotism. At least 20 complaints were submitted to the Constitutional Court regarding alleged violations of the code of ethics and behavioral guidelines for judges in Constitutional Court Decision Number 90/PUU-XXI/2023. All complaints were followed up by the MK Honorary Council (MKMK).